Coronavirus: A punishment, Trail or Message from Allah? An overview of Islamic Teachings (Al-Qamar, 2021)
The aim of this research is to find out Islamic teachings regarding the current pandemic of Covid-19 that whether it is punishment or trial or message from Allah? Starting with the description of corona virus as disease and its effects, the article gives a picture of Islamic teachings followed by findings and conclusion. It shows that regardless of the difficulties we are facing in Covid-19, Allah wants to draw His servants close to Him, and intends good for them. We must draw solace from the fact that Allah shows more mercy to His servants compared to a mother’s mercy for her child. To deal with hardships and earn Allah’s pleasure, we must regularly offer our gratitude towards Allah. This will also improve our health, both physically and mentally. Allah has promised the protection of His servants that ask for His mercy and forgiveness. Just like other calamities this pandemic can be face with piety, repentance, and patience. Along with faith in Allah, we should show clinical attitude in dealing with the pandemic, we should follow the guidelines of health experts, and take necessary measures along with rely upon Allah.
Keywords: Covid-19; punishment; trial, message; Islamic Teachings